Framing Analysis of Indonesian National Police After the Death of Affan Kurniawan in Media Kompas.com and Detik.com Period 28-31 August 2025 - Ida Kusuma Ningrum; Herlambang Jati Kusumo (Jogjakarta Communication Conference (JCC), 2026)
The demonstration at the end of August 2025 attracted public attention because a civilian died after being hit by a Brimob car. This study aims to analyze how online media, specifically Kompas.com and Detik.com, frame news regarding this incident and how the media constructs reality concerning the image of the police institution. The method used is a qualitative descriptive approach with framing analysis. Data was collected through observation techniques of news texts from the period of August 28–31, 2025. This study analyzes 6 news articles, 3 from Kompas.com and 3 from Detik.com. The results show that the two media outlets have differences in framing the event. Kompas.com focuses more on human rights issues, security policies, and shaping the image of the police as an institution facing a crisis of trust. Meanwhile, Detik.com highlights individual violations by officers as well as the process of internal disciplinary enforcement, thus portraying the Indonesian National Police (Polri) as a responsive institution that is undergoing reform. Both share similarities in giving negative assessments of officer actions and supporting resolution steps through internal police mechanisms. Reporting by Kompas.com and Detik.com not only conveys facts but also constructs social reality regarding the Polri, which influences public perception of the police institution.